Enabling Ultrathick Electrodes via a Microcasting Process for High Energy and Power Density Lithium‐Ion Batteries. Issue 38 (19th July 2022) - Plateau, Tazdik Patwary; Pham, Hiep; Zhu, Yaqi; Leu, Ming; Park, Jonghyun
Abstract: Thickening electrodes is one effective approach to increase active material content for higher energy and low‐cost lithium‐ion batteries, but limits in charge transport and huge mechanical stress generation result in poor performance and eventual cell failure. This paper reports a new electrode fabrication process, referred to as µ‐casting, enabling ultrathick electrodes that address the trade‐off between specific capacity and areal/volumetric capacity. The proposed µ‐casting is based on a patterned blade, enabling facile fabrication of 3D electrode structures. The study reveals the governing properties of µ‐casted ultrathick electrodes and how this simultaneously improves battery energy/power performance. The process facilitates a short diffusion path structure that minimizes intercalation‐induced stress, improving energy density and cell stability. This work also investigates the issues with structural integrity, porosity, and paste rheology, and also analyzes mechanical properties due to external force. The µ‐casting enables an ultrathick electrode (≈280 µm) that more effectively utilizes NMC‐811 (LiNi0.8 Mn0.1 Co0.1 O2 ) cathode and mesocarbon microbeads anode active materials compared to conventional thick electrodes, allowing high‐mass loading (35.7 mg cm −2 ), 40% higher specific capacity, and 30% higher areal capacity after 200 cycles, high C‐rate performance, and longer cycle life. Abstract : Thick electrodes are important for achieving higher performance for lithium‐ion batteries but have several limitations to implementation, including poor energy and power densities and mechanical stability. This work introduces a micro‐casting process to enable ultra‐thick electrodes (≈280 µm) and ultra‐high mass loading (35.7 mg cm −2 ) that address the key issues with fabricating thick electrodes without compromising different performance metrics.